2017
DOI: 10.1111/1541-4337.12256
|View full text |Cite
|
Sign up to set email alerts
|

Compressed Baker's Yeast: Mapping Patents on Post‐Fermentation Processes

Abstract: In the baking industry, fresh yeast is generally available as a compressed paste containing about 70% moisture. While much literature has been published on its growth conditions in fermentation tanks, little information may be obtained on the final steps of baker's yeast production. In this review, 226 patents were found on the separation of yeast cells from spent growth media as well as its dewatering, forming, and packaging in the compressed form. The latter corresponded to 21% of 1096 unique families of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 34 publications
0
24
0
1
Order By: Relevance
“…It was previously reported that most of the early inventors on active dry yeast worked in a rather empirical manner and had little knowledge of other patents or information disclosed in scientific articles (Gélinas, ). It is also known that thorough search of the patent literature would allow a unique perspective on the long‐term development of baker's yeast technology (Gélinas, ). We now report that several critical lessons in the production of active dry yeast could only be learned from the patent literature.…”
Section: Long‐term Evolution Of Patents and Applied Scientific Articlesmentioning
confidence: 99%
See 4 more Smart Citations
“…It was previously reported that most of the early inventors on active dry yeast worked in a rather empirical manner and had little knowledge of other patents or information disclosed in scientific articles (Gélinas, ). It is also known that thorough search of the patent literature would allow a unique perspective on the long‐term development of baker's yeast technology (Gélinas, ). We now report that several critical lessons in the production of active dry yeast could only be learned from the patent literature.…”
Section: Long‐term Evolution Of Patents and Applied Scientific Articlesmentioning
confidence: 99%
“…With 62 patents or 22% of total, inventors from the U.S.A. had the greatest interest in long‐term preservation of active yeast starters for foods. This contrasts with the production of fresh baker's yeast for which inventors from Germany were the most active to get patent protection (Gélinas, ). German and French citizens each had 14% of the patents, and other inventors were from Great Britain (12%), Japan (6%) and, with less than 5% of total, China, The Netherlands, Austria, Belgium, Sweden, Denmark, and 15 other countries.…”
Section: Inventorsmentioning
confidence: 99%
See 3 more Smart Citations